2015
DOI: 10.1007/s10725-015-0026-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of maize mature embryos from an elite maize hybrid Zhengdan958 and its parental lines

Abstract: Utilization of heterosis is one of the most outstanding advancements in plant breeding. However, its genetic basis is not well understood. We used digital gene expression technology to investigate the transcriptomes of the mature maize embryo of an elite maize hybrid Zhengdan958 and its parental lines to screen differentiallyexpressed genes and to study their relationship to heterosis. In the study, we found five expression patterns, including co-silence expression of parental lines (754 genes), parental-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…According to the differences in expression between hybrids and their parental lines, genes can be classified into five expression patterns, namely co-silence expression of the parental lines (Type I: genes are expressed in both of the parental lines, but not in F 1 hybrid), parental-specific expression (Type II: genes are expressed only in one of the parental lines), hybrid-specific expression (Type III: genes are expressed only in F 1 hybrid), single-parental consistent expression (Type IV: genes are expressed in F 1 and one of the parental lines), and co-expression of the hybrid and parental lines (Type V) [26]. In the present study, under the control conditions, a total of 288, 1459, 93, and 1713 genes were identified for Types I to IV, respectively, whereas 116, 1478, 153, and 2321 genes were detected for the four groups under heat treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the differences in expression between hybrids and their parental lines, genes can be classified into five expression patterns, namely co-silence expression of the parental lines (Type I: genes are expressed in both of the parental lines, but not in F 1 hybrid), parental-specific expression (Type II: genes are expressed only in one of the parental lines), hybrid-specific expression (Type III: genes are expressed only in F 1 hybrid), single-parental consistent expression (Type IV: genes are expressed in F 1 and one of the parental lines), and co-expression of the hybrid and parental lines (Type V) [26]. In the present study, under the control conditions, a total of 288, 1459, 93, and 1713 genes were identified for Types I to IV, respectively, whereas 116, 1478, 153, and 2321 genes were detected for the four groups under heat treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that Types I to IV are associated with qualitative differences in gene expression, meanings presence/absence variation of these genes. Type V is associated with quantitative differences in gene expression, and the difference in expression patterns between hybrids and their parental lines is predominantly associated with this type [3, 26]. A total of 12 classes of DEGs were defined according to the expression pattern in the hybrid relative to its parental lines in the present study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result showed that a large portion of differential genes were not expressed in mature embryos. In the present study, several DEGs detected by digital gene expression profiling were already validated by quantitative RT-PCR [ 13 ].…”
Section: Discussionmentioning
confidence: 93%